Interface para cálculo de perdas técnicas com OpenDSS - Quadros, Geison Bittencourt (Universidade do Vale do Rio dos Sinos, 2022)
This work addresses the calculation of technical losses in energy distribution networks, based on Annex VII of Normative Resolution No. 956/2021 of the regulatory entity Agência Nacional de Energia Elétrica - ANEEL, of Brazil. Since it is the responsibility of the distributors to calculate and estimate technical losses using this method, the state of the art in the subject is constantly growing in the country, however, the hiring of proprietary software stands out in terms of cost and application, thus making it possible to take advantage of free software such as OpenDSS to enable this type of technical loss analysis. Consequently, the purpose of this work is to create a computational tool for calculating technical losses according to the method guided by ANEEL, which properly has a easy-to-use graphic interface and that it is possible to simulate conductor replacement works in the distribution analyzing the impact on technical energy losses. Thus, knowledge of Python language is applied with integration with the OpenDSS software, provided by the Electric Power Research Institute - EPRI, as well as the use of the library OpenDSSDirect to comply with ANEEL’s power flow calculation method, in which calculation repetition routines are implemented, together with the daily mode of OpenDSS, allowing the monthly calculation of the technical losses of an already modeled network for use in the software. In this way, the work reached the proposed objectives, and the tool proved to be functional, the friendly interface and intuitive, the results achieved in the calculation of technical losses were consistent with the history used as a reference for comparison, as well as the difference found between the tool calculation and the loss history, was below 2.5% for the simulations carried out in a sample of the distributor’s feeders, keeping below the assumption of up to 5% of difference adopted in the methodology. In the same way, the reconductor function proved to be useful for the cases in which it was applied, thus being able to estimate which work of this purpose has greater impact on the distributor’s technical losses.
Keywords: Perdas de energia; Perdas técnicas; Fluxo de potência; Interface Python; OpenDSS; Energy losses; Technical losses; Power flow; Python interface